ALLERGY - Mullajanova Gulnigor Ilhom kizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: Allergies are an overreaction of the immune system to substances that are normally harmless. These substances, called allergens, can be found in a wide range of environmental sources, such as foods, dust, pollen, animal dander, and certain medications.